Kinerja Lembaga Perkreditan Desa (LPD) Adat Demayu Desa Singakerta Kecamatan Ubud Kabupaten Gianyar - NI MADE MITA SINTYA PRADNYANI; I KETUT SUAMBA; I GUSTI AA LIES ANGGRENI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2017)
Performance of Village Credit Instituion (LPD) of DemayuSingakerta Village Ubud District Gianyar Regency The Village Credit Institution (LPD) of Demayu is an institution that plays a role inthe economy of the Indigenous Village of Demayu and as one of the financialinstitutions in rural agriculture. The development and progress of Village CreditInstitutions can be seen through some of the performance namely the financial andthe management performances. The purpose of the study was to determine thefinancial performance by using the profit-oriented ratio of financial institutions andthe management performance of the Village Credit Institution (LPD) of Demayu interms of internal and external aspects. The analytical method used to assess thefinancial performance was conducted by using profit-oriented ratio analysis offinancial institutions while the assessment of the management performance can beseen from two aspects, i.e. the internal and the external performances. Internalperformance can be analyzed from the employee satisfaction aspect and the externalperformance can be seen from the customer satisfaction aspect as measured by Likertscale. Based on the findings of the research, it can be concluded that the VillageCredit Institution (LPD) of Demayu financial performance evaluated from currentratio, debt to asset ratio, total asset turnover were in very unfit category, while the netprofit margin was fit. The management performance in terms of internal aspectobtained an overall average score of 3,97% that categorized as satisfied while theperformance of management in terms of external aspects obtained an overall averagescore of 4.09% that is also categorized as satisfied . Suggestions that can be given:the Village Credit Institution (LPD) of Demayu should further foster their owncapital so that assets increase without increasing the debt; one of them is by way ofincreasing credit distribution activities to the community, for performancemanagement in terms of internal aspects, the management should more oftencommunicate and interact with employees, for the management performance viewedfrom the external aspect, the management should pay more attention and improve thequality of service, and every activity carried out on the Village Credit Institution(LPD) of Demayu should be more emphasized on the concept of Tri Hita Karana.